Truth in the time of fear: Adiós, Ayacucho 's poetics of memory and the Peruvian transitional justice process - Cala Buendía, Felipe (International journal of transitional justice, 2012)
The 1986 short novel, Adiós, Ayacucho ( Farewell, Ayacucho ), by Peruvian writer Julio Ortega, can be read as a set of aspirational claims regarding the, at the time, nascent transitional justice discourse. Analyzed against the findings of the Peruvian Truth and Reconciliation Commission about the same events it portrays, Ortega's novel opens a productive discussion about the way memory - or, rather, memories - should be constructed in the wake of the armed conflict. As the disjointed narration of a fragmented body's failed quest for whole(some)ness, the text advocates for a decentralized process of memory building. If transitional justice is to attain its fundamental aim of reinstating and enhancing citizenship in the wake of massive human rights violations, the novel seems to argue, it should engulf not only centralized institutional attempts at memory building but also alternative narratives that recognize the plurality of perspectives and voices that plague an inevitably fragmented social body.